2.5x+50.6=7.4-8.3x

Simple and best practice solution for 2.5x+50.6=7.4-8.3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2.5x+50.6=7.4-8.3x equation:


Simplifying
2.5x + 50.6 = 7.4 + -8.3x

Reorder the terms:
50.6 + 2.5x = 7.4 + -8.3x

Solving
50.6 + 2.5x = 7.4 + -8.3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8.3x' to each side of the equation.
50.6 + 2.5x + 8.3x = 7.4 + -8.3x + 8.3x

Combine like terms: 2.5x + 8.3x = 10.8x
50.6 + 10.8x = 7.4 + -8.3x + 8.3x

Combine like terms: -8.3x + 8.3x = 0.0
50.6 + 10.8x = 7.4 + 0.0
50.6 + 10.8x = 7.4

Add '-50.6' to each side of the equation.
50.6 + -50.6 + 10.8x = 7.4 + -50.6

Combine like terms: 50.6 + -50.6 = 0.0
0.0 + 10.8x = 7.4 + -50.6
10.8x = 7.4 + -50.6

Combine like terms: 7.4 + -50.6 = -43.2
10.8x = -43.2

Divide each side by '10.8'.
x = -4

Simplifying
x = -4

See similar equations:

| 3n^3=108n | | 26-(3x+12)+11-4(x+1)=0 | | 5xy+4yz-9xz-5xy= | | 6-3n=30 | | f(x)=3(cos(3x)) | | 4t^2+31t-8=0 | | Xsquared=72 | | 0.13+0.7(x-2)=0.01(3x-4) | | x-7.7=8.5 | | (5x+4)(5x-6)= | | (5+3z)(3+5z+9z^2)= | | x^2+y^2-20x+12y+134=0 | | 5.9=8.3-0.3x | | y^2-9y+12=0 | | .10x+.25(x+6)+.05*4(x+6)=3.80 | | 4x(6)+2x(6)=-12 | | 2(4v-18)-6v=3(2v-40) | | 6p-5=-7+4p | | 3/4n-24 | | .10x+.25(x+6)+.05*4(x+6)= | | 8n-29=-2+3n | | .75(x-8)=12 | | x+7x+4=180 | | 1384.74=r^2*3.14 | | -13h=6h+114 | | a/5=a-3/5 | | 138.74=r^2*3.14 | | 5(3+5x)-3=137 | | 5y-4=5y+6 | | 2v-19=5v-10 | | 5x^2-3(-2)= | | 4x^2+2x-2=3 |

Equations solver categories